La Puebla de los Pardos en el siglo XVII - Cáceres Gómez, Rina (Revista de historia., 1996)
An explanation of how the black, mulatto, and “pardo” population of the Puebla de los Pardos participated in all aspects of urban life in the city of Cartago, the colonial capital of Costa Rica.